Institutional Transformation of Accounting and Auditing in Non-Profit Organizations: International Standards and Kazakhstani Practice - Makashova , А.Ж.; Baymukhanova, С.Б. (Journal of Economic Research & Business Administration, 2025)
The article is devoted to the analysis and rethinking of approaches to accounting and accountability in non-profit organizations (NPOs) in Kazakhstan. With the globalization of standards and the increasing demand for transparency, NPOs face a number of challenges related to regulatory inconsistency, the limited implementation of international standards (IPSAS, IFR4NPO), staff shortages, and fragmented digitalization. The study is based on the frameworks of institutional theory, public value theory, and stakeholder theory, and applies a mixed methodological approach. The purpose of the study is to identify institutional factors and methodological approaches that influence the development of accounting and auditing systems in Kazakhstan’s non-profit sector, as well as to develop an adapted model of management accounting and accountability oriented toward mission-driven governance and public legitimacy. To achieve this goal, the following tasks are set: to analyze the theoretical and methodological foundations of accounting and accountability in NPOs; to conduct a comparative analysis of international standards and Kazakhstani practice; to identify key problems and institutional barriers affecting the quality of reporting; to develop quantitative indices of financial accountability, staff efficiency, and accounting system maturity; to construct an integrated model of management accounting (MAS); and to define directions for reforms aimed at enhancing transparency, sustainability, and trust in the sector. Key words: non-profit organizations, financial accountability, institutional theory, management accounting systems (MAS), IFR4NPO, IPSAS standards